2010
DOI: 10.1104/pp.110.164178
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Analyses ofEXO70Genes in Arabidopsis Implicate Their Roles in Regulating Cell Type-Specific Exocytosis

Abstract: During exocytosis, Golgi-derived vesicles are tethered to the target plasma membrane by a conserved octameric complex called the exocyst. In contrast to a single gene in yeast and most animals, plants have greatly increased number of EXO70 genes in their genomes, with functions very much unknown. Reverse transcription-polymerase chain reactions were performed on all 23 EXO70 genes in Arabidopsis (Arabidopsis thaliana) to examine their expression at the organ level. Cell-level expression analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 57 publications
(77 reference statements)
5
107
1
1
Order By: Relevance
“…We anticipated that another EXO70 isoform(s) adopted the essential 405 role of sporophytic EXO70A1 in the male gametophyte. Our list of potential pollen EXO70 406 isoforms (EXO70A2, C1, C2, F1, H3, H5, and H6) is consistent, except for EXO70A2, with a 407 comprehensive study on expression of all EXO70 family members in various tissues based on 408 semi-quantitative RT-PCR and promoter activity by Li et al (2010). The EXO70C2 409 expression in later stages of pollen development was also proved by real-time PCR and RNA 410 in situ hybridization (Lai, 2016).…”
Section: Exo70c2 Is a Key Factor For Efficient Pollen Tube Growth 402mentioning
confidence: 87%
See 2 more Smart Citations
“…We anticipated that another EXO70 isoform(s) adopted the essential 405 role of sporophytic EXO70A1 in the male gametophyte. Our list of potential pollen EXO70 406 isoforms (EXO70A2, C1, C2, F1, H3, H5, and H6) is consistent, except for EXO70A2, with a 407 comprehensive study on expression of all EXO70 family members in various tissues based on 408 semi-quantitative RT-PCR and promoter activity by Li et al (2010). The EXO70C2 409 expression in later stages of pollen development was also proved by real-time PCR and RNA 410 in situ hybridization (Lai, 2016).…”
Section: Exo70c2 Is a Key Factor For Efficient Pollen Tube Growth 402mentioning
confidence: 87%
“…425 Importantly, our analyses of the pollen-expressed EXO70 paralogs indicate, that the 426 multiplicity of the EXO70 family in land plants could not be explained only based on the 427 tissue/cell-specific expression as proposed by Li et al (2010), but most probably several 428 versions of the exocyst complex are active in land-plant cell types (Žárský et al, 2009, Žárský 429 et al, 2013). 430…”
Section: Exo70c2 Is a Key Factor For Efficient Pollen Tube Growth 402mentioning
confidence: 96%
See 1 more Smart Citation
“…These selected genes either had no reported T-DNA lines available (Borg et al, 2011;Li et al, 2010) or were thought to be involved in the selfincompatibility (SI) signaling pathway (Takayama and Isogai, 2005;Kakita et al, 2007), which requires the C24 genetic background for functional analysis. From a total of 7,844 bp fragments screened, 73 mutations were (Table 2).…”
Section: Detection Of Ems Mutations From the C24till Collectionmentioning
confidence: 99%
“…Although the divergence of expression profiles of these paralogues in different tissues (9) suggests tissue-specific roles in different cellular processes, the genetic redundancy has rendered the analysis of individual components problematic. Intriguingly, protoplast transfection of GFP-tagged versions of EXO70 has revealed that only a subset of these paralogues are recruited to membranes (10 (11), EXO70C1 is involved in pollen tube growth (9), and EXO70B1 is involved in autophagy-related vacuolar transport (12). Genetic knockout of EXO70A1, the most abundant paralogue in Arabidopsis, causes pleotropic defects, as may be expected from interfering with a vital cellular process such as exocytosis (13).…”
mentioning
confidence: 99%